Fibroblast Activation Protein-Alpha is a Prognostic Biomarker Associated With Ferroptosis in Stomach Adenocarcinoma - Lyu, Zejian; Li, Yafang; Zhu, Dandan; Wu, Sifan; Hu, Fei; Zhang, Yu; Li, Yong; Hou, Tieying (Frontiers in Cell and Developmental Biology, 2022)
Background: The potential role of fibroblast activation protein-alpha (FAP) in modulating the progression and invasion of stomach adenocarcinoma (STAD) has not yet been comprehensively investigated. This study aimed to explore the role of FAP in STAD and the underlying association between FAP and the tumor microenvironment (TME) and ferroptosis. Methods: Overall survival was analyzed to evaluate the prognostic value of FAP based on gene expression data and clinical information on STAD. Associations between FAP expression, clinical parameters, and immune characteristics were comprehensively analyzed. The ferroptosis-related patterns of STAD samples were investigated based on 43 ferroptosis-related genes, and the correlation between these clusters and clinical characteristics were evaluated. The possible biological functions and pathways were explored using gene set enrichment analysis (GSEA). Results: FAP was identified as a novel biomarker that significantly contributed to the poor prognosis of STAD (hazard ratio =1.270, P=0.013). FAP overexpression was associated with a more advanced tumor stage in STAD. The close relationship between FAP and the TME was validated. Four distinct ferroptosis-related clusters (A–D) were evident. Evaluating ferroptosis-related clusters could illustrate the stages of STAD and patient prognosis. Cluster C displayed the lowest FAP expression and a better prognosis than the other clusters. The different clusters were linked to different biological mechanisms, including epithelial-mesenchymal transition and immune-relevant pathways. Conclusions: FAP is a promising biomarker to distinguish STAD prognosis and is associated with the TME and ferroptosis in STAD.